A numerical method for the wave equation subject to a non-local conservation condition - Ang, Whye-Teong (Applied numerical mathematics, 2006)
A numerical method based on an integro-differential equation and local interpolating functions is proposed for solving the one-dimensional wave equation subject to a non-local conservation condition and suitably prescribed initial-boundary conditions. To assess its validity and accuracy, the method is applied to solve several test problems.